2011
DOI: 10.1007/s00439-011-1109-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of Tibetan high-altitude adaptation

Abstract: Some highland populations have genetic adaptations that enable their successful existence in a hypoxic environment. Tibetans are protected against many of the harmful responses exhibited by non-adapted populations upon exposure to severe hypoxia, including elevated hemoglobin concentration (i.e., polycythemia). Recent studies have highlighted several genes subject to natural selection in native high-altitude Tibetans. Three of these genes, EPAS1, EGLN1 and PPARA, regulate or are regulated by hypoxia inducible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 51 publications
4
105
2
Order By: Relevance
“…Importantly, studies have shown evidence of natural selection among HIF pathway and hypoxia-related genes (Table 3B). Two genes are particularly noteworthy because of the consistency with which they have been observed in these studies (Simonson et al 2012;Petousi and Robbins 2014). One is HIF2A, which shows evidence of positive directional selection (selection for advantageous mutations that increase fitness of carriers) in all of these genome-wide analyses (Beall et al 2010;Bigham et al 2010;Simonson et al 2010;Yi et al 2010;Peng et al 2011a;Wang et al 2011;Xu et al 2011), and both HIF2A SNP genotypes and haplotypes significantly associate with low hemoglobin concentration in Tibetans (Beall et al 2010;Yi et al 2010).…”
Section: Tibetan Adaptation To High Altitude and Genetic Analysesmentioning
confidence: 61%
See 1 more Smart Citation
“…Importantly, studies have shown evidence of natural selection among HIF pathway and hypoxia-related genes (Table 3B). Two genes are particularly noteworthy because of the consistency with which they have been observed in these studies (Simonson et al 2012;Petousi and Robbins 2014). One is HIF2A, which shows evidence of positive directional selection (selection for advantageous mutations that increase fitness of carriers) in all of these genome-wide analyses (Beall et al 2010;Bigham et al 2010;Simonson et al 2010;Yi et al 2010;Peng et al 2011a;Wang et al 2011;Xu et al 2011), and both HIF2A SNP genotypes and haplotypes significantly associate with low hemoglobin concentration in Tibetans (Beall et al 2010;Yi et al 2010).…”
Section: Tibetan Adaptation To High Altitude and Genetic Analysesmentioning
confidence: 61%
“…For well over a century, the unique suite of physiological adaptations to chronic hypoxia observed among long-term resident populations has been well documented (for review, see Hornbein and Schoene 2001). Studies conducted over the past decade as well as more recent genomic studies support a genetic basis for these adaptations (Simonson et al 2012;Scheinfeldt and Tishkoff 2013). Interestingly, the patterns of genetic changes differ among the three populations.…”
mentioning
confidence: 92%
“…Separate genomic studies detailed variants in Tibetan highlanders in the genes EPAS1 (encoding HIF-2α) and EGLN1 (one of the prolyl hydroxylases that regulate HIF1α/2α). [100][101][102][103][104] Furthermore, a genetic mutation resulting in HIF-2α overexpression was associated with development of PH. 105 Andeans have lived at high altitude for approximately 11,000 years.…”
Section: Mechanisms Of Hph: Lessons From High-altitude Genomicsmentioning
confidence: 99%
“…These studies consistently identified genetic signatures in the EGLN1 (also known as prolyl hydroxylase domain protein 2, or PHD2) 2 and EPAS1 (also known as hypoxia-inducible factor-2␣, or HIF2A) genes in the Tibetan population (10).…”
mentioning
confidence: 87%